2018
DOI: 10.1016/j.bbrc.2017.12.116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CX3CR1 reduces cell motility and viability in pancreatic adenocarcinoma epithelial cells

Abstract: Increased expression of the chemokine CXCL1 and its sole receptor, CXCR1 have been correlated with poor pancreatic cancer patient survival and time to recurrence, as well as with pancreatic perineural invasion. We have previously shown that metastasis of prostate and breast cancer is in part driven by CXCL1, and have developed small molecule inhibitors against the CXCR1 receptor that diminish metastatic burden. Here we ask if inhibition of this chemokine receptor affects the phenotype of PDAC tumor cells. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Besides, we further revealed that majority of infiltrated M2 macrophages strongly expressed CX3CR1, and both recombinant CX3CL1 and NP cells significantly induced M2 polarization of RAW264.7. While this effect was totally reversed by si-CX3CL1 or JMS-17-2, which has been frequently used as an inhibitor of CX3CR1 [ 17 ], indicating that CX3CL1/CX3CR1 axis was involved in the recruitment of M2 macrophages in the degenerated NP tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we further revealed that majority of infiltrated M2 macrophages strongly expressed CX3CR1, and both recombinant CX3CL1 and NP cells significantly induced M2 polarization of RAW264.7. While this effect was totally reversed by si-CX3CL1 or JMS-17-2, which has been frequently used as an inhibitor of CX3CR1 [ 17 ], indicating that CX3CL1/CX3CR1 axis was involved in the recruitment of M2 macrophages in the degenerated NP tissue.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a few anti-FKN drugs have been identified in the research market, including E6011 and JMS-17-2. The use of E6011 has been focused on assessing its effects on inflammatory conditions such as rheumatoid arthritis (RA) and Crohn's disease [89][90][91][92][93][94], whilst JMS-17-2 was particularly emphasised for its effects as an anti-cancer medication [100,101]. Tanaka et al had used a humanised monoclonal antibody called E6011 as its anti-FKN pharmacological therapy [102].…”
Section: Alternative Drugs To Target Fractalkine Signallingmentioning
confidence: 99%
“…The CX3CL1-CX3CR1 axis has a direct action on molecules that facilitate invasion and metastasis, such as extracellular matrix metalloproteinases (MMPs), enzymes that have a central role on tissue remodeling. In studies carried out in the human cell line A549, it was found that knocking down CX3CL1 reduced MMP-2 and MMP-9 expression [97], and studies on pancreatic adenocarcinoma cells showed that the pharmacological inhibition of CX3CR1 with the selective antagonist JMS-17-2, decreased their motility and metastasis on a murine model of carcinogenesis [98,99]. It is important to evaluate in future research whether differential fragments of CX3CL1 are generated in the tumor microenvironment due to changes in expression patterns of metalloproteases in tissues undergoing remodeling.…”
Section: Cx3cl1-cx3cr1 In Cancermentioning
confidence: 99%